Order And Teach Of Sholat In Perspective Suluk Linglung Sunan Kalijaga - Fatchullah Zarkasi (Yayasan Al-Afif, 2025)
This research is to know more about Humans. Social and individual creatureswho are interconnected. The difference between one person or group andanother is an unavoidable law of nature (sunnatullah). Connect to God andGod Creation. This research is a qualitative study using a case studyapproach. Qualitative research collects data obtained through observation anddocumentary research. The data collected and analyzed are described asdescribed above. Sholat is a movement and action in the mystical dimension:past, present, and future. In the movement of standing up straight, foldingyour arms creates calmness in your mind, while folding your arms increasesyour concentration and unifies all your movements. Then bow before theCreator. Then bow down, that is, face the form of Allah. In the Suluk texts,especially in Episode V of Pupuh Kinanti, compulsory prayers are taught andordered according to the Shari’a taught by the great Prophet MuhammadSAW.